1989
DOI: 10.1515/zna-1989-0610
|View full text |Cite
|
Sign up to set email alerts
|

Internal Cation Mobilities in the Molten Binary System(Na,NH4)NO3

Abstract: Relative differences in the internal cation mobilities in the molten binary system (Na, NH4)NO3 have been measured by Klemm's countercurrent electromigration method at NaNO3 mole fractions 0 0.3 and temperatures 433-453 K. Also the densities and electric conductivities of this system have been measured. From these data the internal cation mobilities, bNa and bNH₄, were calculated. Under all accessible conditions, bNH₄ is greater than bNa. The results are discussed in terms of the interaction between unlike ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…c The values are calculated from the data book [61]; for NH 4 NO 3 , the data are taken from [29]. d For NaNO 3 , the values at 300 • C are extrapolated ones, since the melting point is a little higher.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…c The values are calculated from the data book [61]; for NH 4 NO 3 , the data are taken from [29]. d For NaNO 3 , the values at 300 • C are extrapolated ones, since the melting point is a little higher.…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been found that, in (Na, NH 4 )NO 3 , NH + 4 is more mobile than Na + under all realizable conditions of temperatures and concentrations [29]. Since NH 4 NO 3 decomposes thermally rather rapidly above 240 • C [60], as mentioned above, the temperature has to be kept below 180 • C and the concentration of NH + 4 , x NH 4 , should be above 0.7, where u Na < u NH 4 at high concentrations of NH 4 NO 3 [29].…”
Section: Mobility Order Ofmentioning
confidence: 98%
See 2 more Smart Citations